2015
DOI: 10.1021/la504890v
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Soft and Hard Proteins onto OTCEs under the Influence of an External Electric Field

Abstract: The adsorption behavior of hard and soft proteins under the effect of an external electric field was investigated by a combination of spectroscopic ellipsometry and molecular dynamics (MD) simulations. Optically transparent carbon electrodes (OTCE) were used as conductive, sorbent substrates. Lysozyme (LSZ) and ribonuclease A (RNase A) were selected as representative hard proteins whereas myoglobin (Mb), α-lactalbumin (α-LAC), bovine serum albumin (BSA), glucose oxidase (GOx), and immunoglobulin G (IgG) were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 50 publications
4
46
0
Order By: Relevance
“…They investigated the binding/unbinding of the human thrombin and its they observed a decrease in the free energy of binding between the thrombin and aptamer, in presence of positive electric fields. This fact is foreseen also by computations, which showed that the application of positive electric field successfully unbinds the thrombin from the aptamer, confirming the influence of electrostatic potential on the thrombin/aptamer complex, accordingly with the literature [31][32].…”
Section: Aptamers In Electrical Nanobiosensorssupporting
confidence: 78%
“…They investigated the binding/unbinding of the human thrombin and its they observed a decrease in the free energy of binding between the thrombin and aptamer, in presence of positive electric fields. This fact is foreseen also by computations, which showed that the application of positive electric field successfully unbinds the thrombin from the aptamer, confirming the influence of electrostatic potential on the thrombin/aptamer complex, accordingly with the literature [31][32].…”
Section: Aptamers In Electrical Nanobiosensorssupporting
confidence: 78%
“…The hydrophobicity map was produced using the hydrophaty index. 14 Recent experimental BSA adsorption studies [15][16][17][18][19][20] have revealed numerous interesting phenomena regarding this protein's behaviour at the surface. However, even modern experimental techniques in isolation have limited access to molecular details such as:…”
Section: Figure1mentioning
confidence: 99%
“…It was shown by ellipsometry and MD simulations that soft proteins, such as glucose oxidase, are less sensitive to changes in the conformation under applied potential once immobilized on a solid surface [186]. CueO [187] and fructose dehydrogenase (FDH) [188] adsorbed on a bare gold electrode at potentials around the potential of zero charge (Epzc) showed the highest direct catalytic activity, suggesting a more favorable enzyme orientation.…”
Section: Effect Of Potential Electric Fieldmentioning
confidence: 99%